Comparative Study on Mechanical Properties of Compacted Clay under Freeze-Thaw Cycles with Closed and Open Systems - Shaohua Xian; Zheng Lu; Hailin Yao; Ran Fang; Jianbo She (Advances in Materials Science and Engineering)
The frost heave and thaw settlement caused by freeze-thaw cycles will seriously affect the engineering properties of soil. This paper attempts to comparatively investigate the deterioration effect of freeze-thaw cycles on the mechanical properties of compacted clay in closed and open systems. The specimens were frozen and thawed from the top to bottom in two systems. The moisture contents and deformations after freeze-thaw cycles were measured. Mechanical parameters of soil were examined through triaxial compression tests. Results show that the moisture content and deformation of soil change evidently with the increase of freeze-thaw cycles in the open system, while these parameters in the closed system change little. In the open system, the attenuation rate of failure strength, elastic modulus, and angle of internal friction of soil subjected to 7 freeze-thaw cycles are all about 2 times as large as that in the closed system and the attenuation rate of cohesion is even 4 times of that in the closed system. These differences reveal that the deterioration effect of freeze-thaw cycles on soil strength is aggravated after water supply. These findings indicate that soil structure damage and moisture content increase is the dominant factor affecting engineering properties of the soil in the open system.